1.
Solution;
Rewrite the solution as;
"\\frac{dy}{dx}x^2(1-x^2)+(3yx^3-xy+y^2)=0"
"\\frac{dy}{dx}x^2(1-x^2)+y(3x^3-x)=-y^2"
Divide by "x^2(1-x^2)"
"\\frac{dy}{dx}+\\frac{y(3x^3-x}{x^2(1-x^2}=\\frac{-y^2}{x^2(1-x^4}"
Divide by -y2
"-\\frac{dy}{dx}+\\frac{(1-3x^2)}{(x-x^3)y}=\\frac{1}{x^2-x^4}"
Let v="\\frac 1y" so that "\\frac{dv}{dx}=\\frac{-dy}{dxy^2}"
Substitute in the equation;
"\\frac{dv}{dx}+\\frac{(1-3x^2)v}{x-x^3}" ="\\frac{1}{x^2-x^4}"
Find the integrating factor;
I.F="e^{\\int{\\frac{1-3x^2}{x-x^3}}}=e^{ln(x^3-x)}=x^3-x"
Multiply all through with the integrating factor;
Substitute 3x2-1="\\frac{d(x^3-x)}{dx}"
"(x^3-x)\\frac{dv}{dx}+\\frac{d(x^3-x)v}{dx}=\\frac{x^3-x}{x^2-x^4}"
Apply reverse product rule:"\\frac{f(dg)}{dx}+\\frac{g(df)}{dx}=\\frac{d(fg)}{dx}"
We have;
"\\frac{d(x^3-x)v}{dx}=\\frac{x^3-x}{x^2-x^4}"
Integrate both sides with respect to x;
("x^3-x)v=-ln(x)+c"
"v=\\frac{-ln(x)+C}{x^3-x}"
But "v=\\frac1y"
"\\frac1y=\\frac{ln(x)+C}{x-x^3}"
Simplify;
y="\\frac{x-x^3}{ln(x)+C}"
2.
Solution;
By distribution,the equation may be written as;
"(2xy+y^3)dx+(xy^2-x^2)dy=0"
Check if the equation is exact,
M="2xy+y^3 ;\\frac{dM}{dy}=2x+3y^2"
N="xy^2-x^2 ;\\frac{dN}{dx}=y^2-2x"
"\\frac{dM}{dy}\\neq\\frac{dN}{dx}" ,the equation is not exact.
Mx-Ny=2x2y+y3x-xy3+x2y=3x2y
Take an integrating factor given as;
I.F="\\frac{1}{Mx-Ny}=\\frac{1}{3x^2y}"
Multiply the given equation with the integrating factor ;
"\\frac{2x+y^2}{3x^2}dx+\\frac{y^2-x}{3xy}dy=0"
The general solution of the problem will be given by;
"\\int{Mdx}+\\int"(Terms of N which are independent of x)
"\\int{\\frac{2x+y^2}{3x^2}}dx+\\int{\\frac{-1}{3y}}dy=C"
"\\frac{2ln(x)}{3}-\\frac{y^2}{3x}-\\frac{ln(y)}{3}=C"
Comments
Leave a comment